Pengaruh Penyediaan Modal dan Pelayanan Karyawan Terhadap Loyalitas Nasabah Pada Koperasi Primkoveri Eromoko - Wonogiri - Dharmawan, Arief; , Drs. H.M. Yahya, M.Si (2015)
The purpose of this study was to determine: 1) Effect of capital adequacy on customer loyalty in the cooperative PRIMKOVERI Eromoko; 2) Effect of service employees on customer loyalty in the cooperative PRIMKOVERI Eromoko; 3) Influence provision of capital and services employees on customer loyalty in the cooperative PRIMKOVERI Eromoko.Jenis this study, quantitative descriptive withdrawal conclusions through statistical analysis. Population in this research is the customer PRIMKOVERI cooperative Eromoko. Samples taken as many as 100 respondents. Technical Collecting data using questionnaires were tested with the test validity and reliability. The data analysis technique used is regression analysis linear, t test, F test, Test R 2 , And the relative contribution analysis and efektif.Hasil obtain a regression line regression equation: Y = 0.799 + 0.346 X 1 + 0,362X2. The equation shows that customer loyalty is influenced by supply capital and service employees. The conclusions drawn are: 1) Provision capital positive effect on customer loyalty in the cooperative PRIMKOVERI Eromoko acceptable. It is based on multiple linear regression analysis (Test t) note that thitung > Ttabel namely 3.941> 0.000 1,980dan significance value <0.05 the relative contribution of 10.33% and 29.03% effective contribution. 2) Services employee positive effect on customer loyalty in the cooperative PRIMKOVERI Eromoko acceptable. It is based on multiple linear regression analysis (Test t) note that thitung > Ttabel namely 4.474> 0.000 1,980dan significance value <0.05 the relative contribution of 25.26% and 70.96% effective contribution. 3). Provision capital and service employees positive effect on customer loyalty in PRIMKOVERI cooperative Eromoko acceptable. It is based on the analysis of variance Multiple linear regression (Test F) note that Fhitung> Ftabel namely 28.383> 3.937 and 0,000 significance value <0.05. 4) The result of the coefficient of determination (R 2 ) amounted to 0.369 shows that the influence exerted by a combination of variables provision of capital and services employees on customer loyalty is of 36.9%, while 63.1% is influenced by other variables. Keywords : Capital , Employee Care , Customer Loyalty